A cursory review of the importance of teacher training: a case study of Pakistan - Azam, Farah; Omar Fauzee, Mohd Sofian; Daud, Yaakob (IDOSI Publications, 2014)
The main purpose of this study is to the cursory surveyof some erstwhile studies on teachers training in the context of Pakistan. The role of education is undeniably crucial in the development of human capital and consequently the entire society. Where, the importance of teacher is widely accepted in making the future of human-being.Teachers are those selected people who having the candle of enlightenment, knowledge and the key to success. The success a nation is depends upon the success of education system, while the success of education system depends upon the quality of teachers, where, the quality of teachers based on the quality of teacher training.Several issues have been found after reviewing some relevant studies on teacher training. In light of the findings, this study suggests that policy makers need to prepare proper education policy in order to improve teacher education, which will ultimately enhance student achievement. Apart from the government, all public, private sectors and degree awarding institutions which are autonomous bodies are required to update the curriculum for teacher training in Pakistan to the internal level.